Antibacterial activity of ruthenium(II) polypyridyl complex manipulated by membrane permeability and cell morphology. Issue 10 (15th May 2015) - Sun, Dongdong; Zhang, Weiwei; Lv, Mengting; Yang, Endong; Zhao, Qian; Wang, Weiyun
Graphical abstract: Here, we presented the antibacterial activity of ruthenium(II) polypyridyl complex RuBP against bacterial cells were due to RuBP could cause membrane damage and destroy membrane integrity, which might eventually induce growth inhibition and bacterial death. Abstract: This study investigates the antibacterial effects of the ruthenium(II) complex RuBP and the mechanism of RuBP action on bacteria. Results show that RuBP can inhibit the growth of Gram-positive bacteria, such as Staphylococcus aureus and Micrococcus tetragenus . Cellular uptake and laser confocal microscopic studies reveal the efficient uptake of RuBP by M. tetragenus cells. Scanning electron microscopic observations of the morphologies of M. tetragenus and S. aureus treated with RuBP further confirm that direct contact of both bacteria with RuBP can damage the cell membrane and membrane integrity, which may eventually induce growth inhibition and bacterial death. After RuBP treatment, the electrical conductivity of the bacterial suspensions increases. Spectroscopic studies and agarose gel electrophoresis indicate that intact DNA and RNA decrease or disappear in RuBP-treated bacterial cells, thus demonstrating that RuBP performs its antibacterial function by increasing the permeability of cell membranes. This study provides new insights for understanding the antibacterial actions of RuBP and designing metal complex antibiotics for other biomedical applications.